The Effect of Job Burnout on Teachers’ Turnover Intentions in Primary and Secondary Schools - The Case of Aksu District - Wang, Longke; Benjasak, Chonlakan; Swatdikun, Trairong (Science, Technology, and Social Sciences Procedia, 2024)
This paper investigates the impact of job burnout on the turnover intentions of primary and secondary school teachers in the Aksu district of Xinjiang, China, using social exchange theory as a lens. Utilizing a quantitative approach, the research engaged 407 teachers through a questionnaire survey, collecting data on the key dimensions of job burnout - emotional exhaustion, depersonalization, and reduced personal accomplishment - and their correlation with teachers’ intentions to leave their profession. The demographic profile of respondents indicated a majority of females, aged 31 - 40 years, with a bachelor’s degree and 6 - 10 years of teaching experience. Descriptive analysis revealed that job burnout is perceived positively, with significant agreement on the aspects of depersonalization and reduced personal accomplishment. Correlation and regression analyses demonstrated a significant positive relationship between job burnout and turnover intention, with each dimension of burnout - emotional exhaustion, depersonalization, and reduced personal accomplishment - having a substantial positive effect on the propensity to leave. The research concludes that job burnout significantly influences teachers’ intentions to leave their jobs, underscoring the necessity for educational administrations to address burnout among faculty. To prevent burnout and reduce turnover rates, it is recommended to provide adequate work resources, enhance work environments, and offer professional development opportunities. The research acknowledges limitations regarding sample diversity and data collection timeframes, suggesting future studies expand sample representation and explore additional factors influencing burnout.